Relating Mandates in the United States for Managing the Ocean to Ecosystem Goods and Services Demonstrates Broad but Varied Coverage - Foran, Christy M.; Link, Jason S.; Patrick, Wesley S.; Sharpe, Leah; Wood, Matthew D.; Linkov, Igor (Frontiers in Marine Science, 2016)
There are numerous ecosystem goods and services (EGS) provided by the ocean. There are also multiple mandates to address this suite of EGS. Which facets of the ocean EGS does this portfolio of mandates collectively address? How are these mandates interrelated? Are there gaps in their coverage of EGS? Are there areas of reinforcement? To elucidate this set of issues, we characterize the portfolio of mandates that a leading U.S. governmental ocean agency, the National Oceanographic and Atmospheric Administration (NOAA), and the subset of those that one of its Line Offices, the National Marine Fisheries Service (NOAA-Fisheries), is responsible for implementing. We link these mandates to a suite of EGS, evaluating the relative degree that each mandate addresses each EGS. The weighted overlap across mandates with respect to EGS was also estimated. Of the nearly 100 NOAA mandates, and the subset of 50 NOAA-Fisheries mandates, there was broad coverage of ocean EGS; every EGS has at a minimum of 9 NOAA mandates that addressed that topic. Food production, habitat provision, genetic resources, recreation, tourism, historical and heritage value, and knowledge and science value were the EGS that had the highest amount of coverage at 30, 42, 50, 39, 38, 34, and 60 NOAA mandates, respectively. There was some reinforcement across mandates, particularly for the top EGS, suggesting that the multiple facets of these EGS are being reasonably well addressed. Seventy percent of mandates informed the same EGS via implementation of the top 10 mandates considered to be the most important for NOAA. The large number of mandates and the overlap in the EGS they address suggest that some form of coordination is warranted, particularly via adoption of an ecosystem-based approach to management.